Literally Speaking - McCarthy, Liam (Lingua Frankly, 2016)
This is a brief overview of the histoy of the word literally. The word literally has been at the heart of a debate between prescriptivist and descriptivist attitudes towards dictionaries and the English language in general so an analysis of the word's history unveils a number of key moments in the word's history that can help or hinder either side's argument. This controversial word's history also interestingly reveals some of the ways that the English language grows and changes over time.